PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN DISCOVERY LEARNING BERORIENTASIKAN KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS - Nurdin Arifin (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This research aims to produce mathematics instructional package for grade 8 junior high school with discovery learning oriented to mathematical reasoning and communication consists of lesson plans and student worksheets. This research was a research and development using ADDIE model. The model consisted of analysis, design, development, implementation, dan evaluation. The subjects of this research were 33 students from one class of SMP N 15 Yogyakarta. The analysis of the validity and practicality were analyzed by converting the actual scores obtained into five scales of qualitative data. The analysis of the effectiveness of the data was conducted by determining the percentage of the students learning mastery. The results of the validation show that the developed instructional package is very valid based on the lesson plans and student worksheets. The results of teacher assessment show that the instructional package is very practical. Based on the results of reasoning ability and mathematical communication tests, instructional package is effective.